Prebiotic supplementation in patients with type 1 diabetes: study protocol for a randomised controlled trial in Canada - Shyamchand Mayengbam; Raylene A Reimer; Sonia Butalia; Carol Huang; Elizabeth Rosolowsky; Munier A Nour; Josephine Ho; Weilan Wang; Shannon Pyke; Heidi Virtanen (BMJ Open)
Introduction Type 1 diabetes (T1D) mellitus is caused by autoimmune destruction of insulin-producing beta-cells, requiring exogenous insulin to sustain life. Achieving near normal blood glucose levels with insulin, a primary goal of diabetes management, carries a significant risk of hypoglycaemia. There is compelling evidence that an abnormal gut microbiota or dysbiosis can increase intestinal permeability (IP) and contribute to dysglycaemia seen in T1D. Given that prebiotic fibre can mitigate dysbiosis, reduce IP and improve glycaemic control, we hypothesise that microbial changes induced by prebiotics contribute to gut and endocrine adaptations that reduce glucose fluctuations, including less hypoglycaemia. In a pilot study, we showed that in children who had T1D for at least 1 year, a 3-month course of prebiotic fibre significantly reduced the frequency of hypoglycaemia. The prebiotic group had an increase in Bifidobacterium with a moderate improvement in IP. Importantly, the prebiotic group maintained their serum C peptide level (marker of residual beta cell function) while the placebo group saw a drop. Given that preserving endogenous beta cell function in patients with T1D, particularly in the first year of diagnosis, reduces hypoglycaemia and glycaemic variability, we propose to examine the effect of prebiotic supplementation in patients with T1D.Methods and analysis This is a multicentre, randomised, double-blind, placebo-controlled study. Individuals (n=144) with T1D will be randomised 1:1 for 6 months to prebiotic (oligofructose-enriched inulin) or placebo (isocaloric maltodextrin). Participants will have three in-person study visits at baseline, 3 months and 6 months. The primary outcome, frequency of hypoglycaemia, will be determined from continuous glucose monitor (CGM) reports and patient blood glucose logs. Secondary outcomes will include glycaemic variability, time-in-range, glycated haemoglobin, stimulated C peptide, IP, serum inflammatory markers, quality of life and fear of hypoglycaemia ratings, as well as gut microbiome and metabolomics analysis. At 9 months, participant CGM data will be used to assess frequency of hypoglycaemia and glycaemic variability at 3 months postintervention.Ethics and dissemination The study received ethical approval from the University of Calgary Conjoint Health Research Ethics Board (REB21-0852). The University of Alberta subsite was granted ethical approval under the province of Alberta’s research ethics reciprocity agreement as a participating site (REB21-0852; pSite00000066). The University of Saskatchewan subsite was granted ethical approval by the Biomedical Research Ethics Board (#4149). Trial findings will be disseminated through peer-reviewed publications and conference presentations.Trial registration number clinicaltrials.gov NCT04963777.